Benefit of Finnish Score As a Risk Assessment Tool for Predicting Type II DM Among Sudanese Population in North Sudan - Khalid Mohammed Noor, Sufian; Mohamed Fagir Farah, Amro; Abdalla Alameen Karar, Nusiba; Osman Elamin Bushara, Sara; Ismaeil Sirri Farah, Sirelkhatim; Salah Eldin Hashim Mohammed Osman, Mohammed; Mustafa Abdelrahim Osman, Mahmoud; Omer Ibrahim Ali, Ali; Adil Ahmed Hassan Kaba, Omnaya; Badi, Safaa (Sudan Journal of Medical Sciences, 2024)
Background: Diabetes mellitus is a major noncommunicable disease worldwide, and its prevalence is rapidly increasing. The Finish score helps in the prediction of the risk of future diabetes development, as well as in the identification of undiagnosed diabetes. The current study was conducted to identify people at risk of developing type II diabetes mellitus in River Nile State, Sudan. Methods: This cross-sectional community-based study was conducted in River Nile state between 2019 October and 2020 March. Data were collected using a questionnaire that included the Finnish Diabetes Risk Score variables from 400 participants after an informed consent. Chi-square test was used to test the associations, with the P-value considered significant when <0.05. Results: The majority of participants (257 [64.3%]) were <45 years old, and 229 (57.3%) were male. The risk of type II diabetes mellitus was found to be low in 187 (46.8%) people and high in 213 (53.2%). Moreover, 128 (32%) had a body mass index (BMI) between 25 and 30 kg/m2, while 46 (11.5%) had >30 kg/m2. A waist circumference of <94 cm was found in 147 (36.8%) males, while only 63 females (15.8%) had a waist circumference of <80 cm. Age, gender, BMI, daily activity, history of hypertension, history of hyperglycemia, and family history of diabetes were all significantly associated with the risk of developing diabetes mellitus (P < 0.001). Conclusion: The Finnish Diabetes Risk Score was found to be useful in facilitating wider access to the risk of type II diabetes among the study population. More than half of the study population were at risk of developing diabetes mellitus.